2020
DOI: 10.1111/medu.14382
|View full text |Cite
|
Sign up to set email alerts
|

Students' social networks are diverse, dynamic and deliberate when transitioning to clinical training

Abstract: Context Transitions in medical education are dynamic, emotional and complex yet, unavoidable. Relationships matter, especially in times of transition. Using qualitative, social network research methods, we explored social relationships and social support as medical students transitioned from pre‐clinical to clinical training. Methods Eight medical students completed a social network map during a semi‐structured interview within two weeks of beginning their clinical clerkships (T0) and then again four months la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(86 citation statements)
references
References 46 publications
(55 reference statements)
0
86
0
Order By: Relevance
“…A face-to-face meeting can be held to explain the dynamics, opportunities, and benefits of the group, as well as the duties acquired once they are accepted. For this, the use of digital marketing has played an important role today, social networks, such as WhatsApp, Twitter, Facebook, and Instagram [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], can be used to welcome and attract the attention of new members [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A face-to-face meeting can be held to explain the dynamics, opportunities, and benefits of the group, as well as the duties acquired once they are accepted. For this, the use of digital marketing has played an important role today, social networks, such as WhatsApp, Twitter, Facebook, and Instagram [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], can be used to welcome and attract the attention of new members [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…To accomplish this Step, we choose to: Create social networks such as Instagram, Facebook, Twitter, and YouTube channel [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. Set goals with defined schedules to disseminate the information so that there is an active production of content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Atherley et al, in fact, have suggested that students adapt to the introduction of clinical clerkship by deliberately modulating relationships based on whether they provide instrumental or emotional support. 2 Their findings lead us to reflect on the need to consciously enable such network evolution for certain subgroups of students given the potential for socioeconomic variables to restrict adaptation and, hence, negatively impact academic success.…”
Section: Social Network Dynamics Throughout Clinical Training-distancmentioning
confidence: 99%
“…3 Contrary to Atherley et al's findings, commuting students have been shown to maintain stronger familial and local relationships, 3 rather than transitioning their social networks when shifting to clinical training. 2 Commuting also has been associated with increasing stress levels amongst medical students, 4 We believe these findings make it imperative that medical training programmes should aim to better integrate commuting students when they transition to clinical clerkship. This would increase the likelihood that they will become better doctors through the provision of supports other students are able to find more naturally.…”
Section: Social Network Dynamics Throughout Clinical Training-distancmentioning
confidence: 99%